Розпізнавання повітряних об’єктів за їх контурами - Зощук, М. М. (ХНУРЕ, 2023)
Applying the discrete Fourier transform to this sequence generates a unique one-dimensional identification sequence of standard-sized values, called Fourier descriptors, which has a number of interesting properties.
Keywords: розпізнавання повітряних об'єктів; контури об'єкта; трансферне навчання; дескриптори Фур’є